Penggunaan Media Risingstar untuk Meningkatkan Pembelajaran IPA pada Siswa Kelas VI Sekolah Dasar - Marsus Efendi (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2018)
The research objective was to improve science learning effectiveness through environmentally-based science learning materials related to their day-to-day life. Pupils’ environment was meant to mediate awareness, comprehension, and solution to science problems logically, critically, accurately and creatively. Prior observation indicated the pupils’ understanding on plants’ fertilization was categorized as low. The research implemented a descriptive qualitative design. The subjects included children at the public elementary school 2 Gedong Tataan, Pesawaran District, Lampung Province. Data were collected by means of RISINGSTAR media, an acronym of ‘independent, crossed, neighbour, bartered‘. Data were analyzed descriptively focusing on the pupils’ learning achievement. Results show that RISINGSTAR media could improve their mean score = 80.33 with minimum master level of 93.33%. Moreover, their learning attitudes were categorized as creative, disciplined, and respected others.